Development of Learning Module for Writing Procedure Text with the Fllipped Classroom Media E-learning Model at SMK Center of Excellence - Dina, Alistiyani Mustika; Rokhman, Fathur; Wagiran, Wagiran (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The eighth independent learning is center of excellence with a new paradigm curriculum. In learning outcomes, the development of teaching module is carried out so that students are able to think creatively. This research aims to (1) Analyze the needs of students’ skills in writing procedure text with the Flipped Classroom learning model using e-learning media for class XI at SMK Center of Excellence in Hospitality Program (2) Develop the learning module for students’ skills in writing procedure text with the Flipped Classroom learning model using e-learning media for class XI at SMK Center of Excellence in Hospitality Program, (3) Measure the feasibility of learning module for students’ skills in writing procedure text with the Flipped Classroom learning model using e-learning media for class XI at SMK Center of Excellence in Hospitality Program. This research method used Research and Development with ten steps developed by Gall and Borg (2019:35), namely (1) Research and Information Collecting, Planning, Develop Preliminary Form of Product (Initial Product Development), Preliminary Field Testing, Main Product Revision, Main Field Testing, Operational Product Revision, Operational Field Testing, Final Revision Product, Dissemination and Implementation. The results of the research indicate: (1) Analysis of module needs from the results of observation, teacher and student interviews, and student and teacher questionnaires, (2) Development of learning module for skills in writing procedure text from material experts is stated “good”, media experts is stated “very good”, and education practitioners is stated “very good”. (3) The feasibility of learning module for skills in writing procedure text from the teacher response scale of score 61 is “very good” and the student’s response is “very good”.